2014
DOI: 10.1038/cdd.2014.195
|View full text |Cite
|
Sign up to set email alerts
|

The MT2 receptor stimulates axonogenesis and enhances synaptic transmission by activating Akt signaling

Abstract: The MT2 receptor is a principal type of G protein-coupled receptor that mainly mediates the effects of melatonin. Deficits of melatonin/MT2 signaling have been found in many neurological disorders, including Alzheimer's disease, the most common cause of dementia in the elderly, suggesting that preservation of the MT2 receptor may be beneficial to these neurological disorders. However, direct evidence linking the MT2 receptor to cognition-related synaptic plasticity remains to be established. Here, we report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 64 publications
0
44
0
Order By: Relevance
“…In support of this, Liu et al. found that melatonin induces axogenesis through MT2 receptors in embryonic hippocampal neurons from the rat . However, we cannot discard other intracellular/nuclear binding sites in the melatonin signaling involved in axonal formation.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In support of this, Liu et al. found that melatonin induces axogenesis through MT2 receptors in embryonic hippocampal neurons from the rat . However, we cannot discard other intracellular/nuclear binding sites in the melatonin signaling involved in axonal formation.…”
Section: Discussionmentioning
confidence: 70%
“…Recently, it was demonstrated that melatonin induces the dendritogenesis process in the hilar zone of the hippocampus through CaM translocation to the soluble fraction and CaM‐kinase II stimulation, indicating that it plays a key role in neuronal development and differentiation in the adult brain . Also, in cultured embryonic hippocampal neurons, melatonin stimulates axonal formation through MT2 receptors and activation of MT1 receptor has been implicated in neurite formation at earlier stages …”
Section: Introductionmentioning
confidence: 99%
“…41,42 The hippocampi of embryos were dissected and trypsinized by TrypLE Express (Invitrogen) for 15 min at 37 C. Dissociated neurons were plated onto poly(D-lysine)-coated (Sigma) coverslips in a 12-well plate or tissue culture dish covered with a glass bottom (WPI) at a higher density (400-600 neurons/mm 2 ) for western blotting and a lower density (100-200 neurons/mm 2 ) for immunofluorescence. Neurons usually attached to the substrate after they grew in the plating medium (DMEM/F12 with 10% fetal bovine serum [FBS] and 100 U/mL penicillin/streptomycin) for 2-4 hr.…”
Section: Primary Hippocampal Neuron Culturementioning
confidence: 99%
“…Protein concentration was quantitated using the BCA Protein Assay Reagent (Pierce). 42,46 Equal amounts of protein were separated by SDS-PAGE (10% gel) and transferred to nitrocellulose membranes. The membranes were blocked with 5% non-fat milk dissolved in PBS (50 mM Tris-HCl, pH 7.6, 150 mM NaCl) for 30 min to 1 hr and were probed with primary antibodies overnight at 4 C. Then the blots were incubated with goat anti-mouse or anti-rabbit conjugated to IRdye 800 (1:15,000; Rockland Immunochemicals) for 1 hr at 25 C. The protein bands were visualized and quantified by the Odyssey infrared imaging system (LI-COR).…”
Section: Western Blottingmentioning
confidence: 99%
“…Furthermore, our investigation revealed that Akt/NF‐κB signaling activated by MT 2 is important for PINK1‐mediated neuronal cell survival under high glucose conditions. The C‐terminal motif of activated MT 2 directly binds to Akt, which leads to regulation of neuronal cell‐related physiology including hypothalamus‐liver communication, axonogenesis, and synaptic transmission . In addition, it has been reported that Akt phosphorylation by melatonin induces neuroprotective effect .…”
Section: Discussionmentioning
confidence: 99%